Surviva : a future ancestral field guide - Luger, Cannupa Hanska, 1979- (Aora, 2025)
"Since 2015 - through a proliferation of forms including sculpture, regalia, film, photography, poetry, painting, and installation - acclaimed multimedia artist Cannupa Hanska Luger has been weaving together strands of a new myth. Collectively referred to as Future Ancestral Technologies, this sprawling series of interrelated works seeks to reimagine Indigenous life and culture in a postcolonial world where space exploration has reduced and reconfigured the earth's population. Part graphic novel, part art book, SURVIVA: A Future Ancestral Field Guide offers readers a view beneath, beyond, and between the lines of Luger's ever-expanding artistic universe. In this ecstatically hybrid work, Luger transforms a 1970s military survival guide through poetic redaction, speculative fiction, and iterative line drawing - deftly surfacing and disrupting the colonial subconscious that haunts this vexed source text. An epic and timely meditation on planetary life in the midst of transformation, SURVIVA boldly presents an earth-based, demilitarized futuredream that foregrounds Indigenous knowledge as critical to humanity's survival." --